"Intertextuality in Algerian Folk Proverbs: The Hadhna Region as a Case Study" - mekran, mourad (El Omda in Linguistics and Discourse Analysis, 2018)
In this presentation, we examine the concept of “proverb and intertextuality” in both classical and modern contexts, among Arabs and in the West. It is essential to begin with the proverb, as it predates intertextuality. Folk proverbs did not emerge in their current form; rather, they developed over time, transmitted across generations, reflecting different mentalities until they reached us and became applicable to our lives. Every era and generation has been distinguished by its own proverbs, some in classical language and some in vernacular, and they remain among the most truthful expressions.